Application of Concept Mapping to Improve Critical Thinking Ability of Human Digestive Material in Grade V Students - Sonta Asilsa Faisalina (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve student learning outcomes in thematic learning class V SDN Ngarus 02 Pati. This research is a classroom action research (PTK) which is carried out in four cycles, each cycle consisting of the planning, implementation, observation and reflection stages. The subjects of this study were class V students of SDN Ngarus 02 Pati for the 2020/2021 academic year, totaling 36 students. Data collection techniques used tests and non-tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the application of concept mapping to improve critical thinking skills in class V SDN Ngarus 02 Pati as evidenced by the percentage of completeness of learning outcomes in the pre-cycle from 17% to 40% in cycle I, to 52% in cycle II, and to 75% in cycle III. And the percentage of critical thinking in the pre-cycle is 63% to 65% in the first cycle, to 66% in the second cycle, and 67% in the third cycle.